Mothers in stress: Hair cortisol of mothers living in marginalised Roma communities and the role of socioeconomic disadvantage - Chovan, Shoshana; Fiľakovská Bobáková, Daniela; Hubková, Beáta; Madarasová Gecková, Andrea; de Kroon, Marlou L A; Reijneveld, Sijmen A (Psychoneuroendocrinology, 2024)
Roma living in marginalised communities are among the most disadvantaged groups in Slovakia. Socioeconomic disadvantage is associated with higher hair cortisol concentrations (HCC), including in parents. The aim of this study is therefore to assess differences in HCC, reflecting the levels of stress, between mothers living in MRCs and from the majority population, to assess the association of socioeconomic disadvantage with HCC, and whether disadvantage mediates the MRC/majority differences in HCC. Participants were mothers of children aged 15-18 months old living in MRCs (N=61) and from the Slovak majority population (N=90). During preventive paediatric visits, visits at community centres and home visits, hair samples and data by questionnaire were collected. HCC differed significantly between mothers living in MRCs and mothers from the majority population, with the mean HCC value being twice as high in mothers living in MRCs (22.98 (95% confidence interval, CI, 15.70-30.30) vs. 11.76 (8.34-15.20), p<0.05). HCC was significantly associated with education, household equipment and household overcrowding, but not with billing, socioeconomic stress and social support. The difference in HCC between mothers living in MRCs and mothers from the majority population was partially mediated by poor house equipment, such as no access to running water, no flushing toilet or no bathroom (the indirect effect of B=7.63 (95% CI: 2.12-13.92)). Practitioners and policymakers should be aware of high stress levels among mothers living in MRCs and aim at enhancing their living and housing conditions.
Keywords: Socioeconomic Disparities in Health; dospělí; Hair; Social Support; Female; Infant; vlasy, chlupy; Adult; Marginalized Roma communities; ženské pohlaví; psychický stres; hydrokortison; Slovakia; lidé; Hydrocortisone; Parental stress; Vulnerable Populations; Hair cortisol concentrations; Social Marginalization; Mothers of small children; Housing conditions; zranitelné populace; matky; Male; kojenec; Romové; Mothers; Socioeconomic Factors; sociální marginalizace; Roma; Slovenská republika; socioekonomické faktory; mužské pohlaví; Socioeconomic disadvantage; Stress, Psychological; sociální opora; socioekonomické nerovnosti ve zdraví; Humans